The Silence of the Lambs (Hannibal Lecter book 2) - Thomas Harris (New York St.Martin's Griffin, 2009)
Thomas Harris' The Silence of the Lambs is a fictional novel that tells the tale of FBI agent Clarice Starling and her quest to find a serial killer who has been abducting women. However, in order to think like a serial killer, she must learn how the mind works in such a criminal.
Keywords: Thriller; Psychological thriller